Comparison of psychological distress, loneliness, and social network structure between Ukrainian war refugees and Polish citizens: a cross-sectional study in Wroclaw - Jaworski, Arkadiusz; Szyszka, Michał; Sosińska, Daria; Tomaszewicz, Nela; Bednarchuk, Romana; Kulawik, Kinga; Piotrowski, Patryk (Frontiers in Public Health, 2025)
BackgroundThe ongoing war in Ukraine has led to widespread displacement and a growing mental health burden among refugees. Understanding the associations between psychological distress, loneliness, and social networks among Ukrainian war migrants is essential for designing effective support strategies.MethodsA cross-sectional survey was conducted between October 2022 and January 2023, including 209 participants (68 Ukrainian refugees and 141 Polish citizens). Standardized instruments were used: the General Health Questionnaire-28 (GHQ-28) to assess psychological distress, the Revised UCLA Loneliness Scale (R-UCLA), and the Courage Social Network Index (CSNI). Statistical analyses included t-tests, chi-square tests, Spearman correlation, and multiple linear regression to assess group differences and associations among variables.ResultsUkrainian refugees reported significantly higher levels of psychological distress, particularly in somatic symptoms and anxiety/insomnia, compared to Polish citizens. No significant differences in loneliness levels were observed between groups. Refugees demonstrated stronger social networks, particularly in family connections. Psychological distress and depressive symptoms were positively associated with higher loneliness, while stronger social networks were negatively associated with loneliness. In multiple regression models, refugee status, greater loneliness, younger age, and psychiatric history significantly predicted higher psychological distress. Conversely, higher psychological distress, older age, and weaker social networks predicted greater loneliness.ConclusionThe findings underscore the heightened psychological burden among Ukrainian refugees and suggest a protective role of family-based social networks against loneliness. Interventions should prioritize culturally sensitive mental health services, facilitate access to care, and leverage familial support systems. Longitudinal studies are warranted to examine changes in psychological well-being over time.